Diversity of Amphibians (Order Anura) in Cibodas Resort Tourism Route, Gunung Gede Pangrango National Park - Rostikawati, Teti; Prasaja, Dimas; Handayani, Ferra (Jurnal Biodjati, 2022)
Cibodas Resort is one of the protected areas in Gunung Gede Pangrango National Park which is capable of supporting amphibian life. Amphibians can be used as bioindicators of environmental quality, especially aquatic ones. Amphibian studies are found to be interesting, but publications on amphibian data, especially at Resort Cibodas, are still rare. The publications regarding amphibian data of the Anura order, especially in the Cibodas Resort, have not been found. This Study aimed to determine the diversity of amphibians of the Order Anura in the Cibodas Resort tourist route. This research was an exploratory research conducted from September to October 2021. The research method used the Visual Encounter Survey method combined with the Line Transect method by following a predetermined path. The data was retrieved through the form of primary data (number of species of the Order of Anura in the Cibodas Resort tourist route). Based on the results of research at 3 sites, 12 species from 6 families were found with 192 individuals. The diversity index is classified as moderate with a value of 2.15, the evenness index is classified as high with a value of 0.86, and the dominance index is classified as low with a value of 0.14. The species that dominate in the 3 observation sites are from the family Ranidae namely Odorrana hosii and Huia masonii, the family Rhacophoridae namely Rhacophorus margaritifer and the family Dicroglossidae namely Limnonectes kuhlii and L. microdiscus.